Моңғолиядан келген қазақтардың қолөнерлеріндегі кейбір ерекшеліктері (Journal of history, 2020)
The article discusses the features arts and crafts, preserved in Mongolian Kazakhs, and transmitted from generation to generation for a long period of time. A cattle breeding is the foundation of economic activity Mongolian Kazakhs, and women doing various things from wool. This, in particular: felt cover, carpets, rugs. The article also discusses the technology of products made of felt, for example, preparation of wool, its distribution on the mat, hot water treatment, compaction, etc., as well as examines the art of embroidery household items such as wall hangings (tus kiіz), mats (syrmaқ), kinds of embroidery and especially its performance.